Development of E-Learning Electrolyte and Nonelectrolyte Solutions based on Rotary Guided Discovery Learning for Senior High School - Silvi Handri; Eko Nevriansyah; Anisa Qisti Mathriul (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2022)
All activities had to be carried out at home during the Covid-19 epidemic, which affected all nations in the world, including Indonesia. This included learning activities at the elementary, secondary, and higher education levels. This study aims to create e-learning electrolyte and non-electrolyte solutions based on rotary guided discovery learning for high schools. Developed E-Learning Electrolyte and Nonelectrolyte Solutions for Senior High School based on Rotary Guided Discovery Learning to support learning during Covid-19. EDR (Educational Design Research), which employs the PLOMP development model, is the sort of study being conducted. A questionnaire instrument for this study's validity and practicality was used at SMA N 8 Padang. Aiken's V was used to evaluate the validation data, and Kunandar's proposed percentage approach—specifically, the % value—was used to study the practicality data (P). Based on Rotary Guided Discovery Learning, Electrolyte and Nonelectrolyte Solutions for Online Learning In practicality testing, the average value of V for SMA/MA is 0.87, with a valid category, and a percent value (P) of 81, with a very high category. The results of this study indicate that e-learning electrolyte solution based on rotary guided discovery learning has been declared valid, practical and can be utilized in the learning process.